Advancing understanding of oat phenology for crop adaptation - Trevaskis, Ben; Harris, Felicity A. J.; Bovill, William D.; Rattey, Allan R.; Khoo, Kelvin H. P.; Boden, Scott A.; Hyles, Jessica (Frontiers in Plant Science, 2022)
Oat (Avena sativa) is an annual cereal grown for forage, fodder and grain. Seasonal flowering behaviour, or phenology, is a key contributor to the success of oat as a crop. As a species, oat is a vernalization-responsive long-day plant that flowers after winter as days lengthen in spring. Variation in both vernalization and daylength requirements broadens adaptation of oat and has been used to breed modern cultivars with seasonal flowering behaviours suited to different regions, sowing dates and farming practices. This review examines the importance of variation in oat phenology for crop adaptation, focussing on the history of the Australian grains industry as an example. Strategies to advance understanding of the genetic basis of oat phenology are then outlined. These include the potential to transfer knowledge from related temperate cereals, particularly wheat (Triticum aestivum) and barley (Hordeum vulgare), to provide insights into the potential molecular basis of variation in oat phenology. Approaches that use emerging genomic resources to directly investigate the molecular basis of oat phenology are also described, including application of high-resolution genome-wide diversity surveys to map genes linked to variation in flowering behaviour. The need to resolve the contribution of individual phenology genes to crop performance by developing oat genetic resources such as near-isogenic lines is emphasised. Finally, ways that deeper knowledge of oat phenology can be applied to breed improved varieties and to inform on-farm decision-making are outlined.